Novel geobacillus microorganism - Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran; Leow, Thean Chor (2008)
A biologically pure culture of Geobacillus Strain T1 bacteria isolated from Palm Oil Mill Effluent capable of producing thermostable lipase T1 gene. The production of thermostable lipase T1 gene from a novel Geobacillus bacterium having a designated as strain T1, was aerobic, gram positive and endospore- forming, rod-shaped. The G+C content of the genomic DNA was 52.6%. On the basic of physiological data, phenotypic traits and molecular analysis, strain T1 represents a novel species within the genus Geobacillus. The thermostable T1 lipase gene was subcloned into the pGEX-4T1 vector with and without signal peptide in prokaryotic system. The 28 amino acid residues signal peptide alter the conformation GST moiety and preventing it from bind to affinity glutathione Sepharose column. By expression and simplification of the purification through single step affinity chromatography shows a specific activity of 292.929 U/mg and 72.55% of fusion lipase was successfully purified with a final recovery of 51.49% and specificity activity of 959.033 U/mg.